Modelamiento de los aspectos intervinientes en el proceso de pauta periodística (2014)
In Chile, the journalistic routine typically responds to a process based largely on intuition, understood as an immediate instinctive reaction to unforeseen events with social relevance. The editors who are in charge of this process, regardless of the type of social information they deal with, make decisions founded primarily on their experience and journalistic instinct, which directly affects the quality of the content and its consistency with the editorial line adopted by the medium. While the advent of new technologies has changed citizens’ access to information, it also has complicated work in the newsroom, regardless of the vehicle.  News is now is a commodity, which reduces the possibilities of a journalistic coup and calls for more novelty. The figure of the editor or gatekeeper is more important than ever before, because of the editor’s responsibility for selecting and prioritizing the news items most relevant to decision-making on the part of citizens. Through in-depth interviews with directors, editors and journalists from the Chilean newspapers, television stations, news agencies and new media used as a reference, the team presenting this study reviewed and systematized the critical moments in journalistic decision-making.  With that information, they designed a generic process known in literature as a “flowchart for modeling business processes” to which the SIPOC methodology subsequently was applied to determine the extent of the process. The RACI matrix was applied to define the activities and roles of those who participate in them. The essential stages of journalism were identified as proposition, decision and follow-up on execution of the news item. At the end of the modeling, validation was done by the directors, editors and journalists of the media used as a reference.